Enhancing public involvement in assistive technology design research. (May 2015) - Williamson, Tracey; Kenney, Laurence; Barker, Anthony T.; Cooper, Glen; Good, Tim; Healey, Jamie; Heller, Ben; Howard, David; Matthews, Martin; Prenton, Sarah; Ryan, Julia; Smith, Christine
Abstract Purpose: To appraise the application of accepted good practice guidance on public involvement in assistive technology research and to identify its impact on the research team, the public, device and trial design. Methods: Critical reflection and within-project evaluation were undertaken in a case study of the development of a functional electrical stimulation device. Individual and group interviews were undertaken with lay members of a 10 strong study user advisory group and also research team members. Results: Public involvement was seen positively by research team members, who reported a positive impact on device and study designs. The public identified positive impact on confidence, skills, self-esteem, enjoyment, contribution to improving the care of others and opportunities for further involvement in research. A negative impact concerned the challenge of engaging the public in dissemination after the study end. Conclusions: The public were able to impact significantly on the design of an assistive technology device which was made more fit for purpose. Research team attitudes to public involvement were more positive after having witnessed its potential first hand. Within-project evaluation underpins this case study which presents a much needed detailed account of public involvement in assistive technology design research to add to the existing weak evidence base. Implications for Rehabilitation The evidence base for impact of public involvement in rehabilitation technology design is in need of development. Public involvement in co-design of rehabilitation devices can lead to technologies that are fit for purpose. Rehabilitation researchers need to consider the merits of active public involvement in research.